2018
DOI: 10.17140/semoj-4-162
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Martial Arts and Bone Health Status in Young and Older Population

Abstract: It is well known that mechanical loading imposed on a bone is important for bone development. Therefore, one of the most effective osteoporosis prevention strategies is by adopting weight-bearing physical activity. Martial arts such as judo, silat, karate, taekwondo and kickboxing are getting popular in recent years. It is generally known that bone's optimum response and adaptation to an applied load or strain during exercise are dependent on many factors, such as characteristics of the strain, i.e. static ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The potency of protecting muscles might be due to the sumac juice antioxidant potency of β-carotene-linoleic acid components. These results highlight the possibility of sumac juice consumption in improving muscle performance among athletes [ 252 ]. Nevertheless, future studies of athletes are warranted.…”
Section: Fat-soluble Vitamins (Fsv)mentioning
confidence: 84%
“…The potency of protecting muscles might be due to the sumac juice antioxidant potency of β-carotene-linoleic acid components. These results highlight the possibility of sumac juice consumption in improving muscle performance among athletes [ 252 ]. Nevertheless, future studies of athletes are warranted.…”
Section: Fat-soluble Vitamins (Fsv)mentioning
confidence: 84%
“…Research has shown that in order to enhance bone mass, it is necessary to place additional forces on the bones beyond the normal weight that is placed on them in daily life ( 37 ). In our study, after a 12-week semi-combat cardio-kickboxing training, significant improvements were found in femoral neck BMD and T-score.…”
Section: Discussionmentioning
confidence: 99%
“…One such study indicated sport site-specific effects on bone strength in adolescent male hockey and soccer players, with increased respective QUS quantitative radial and tibial speed of sound (SOS) measures compared to controls (Falk et al, 2010). The osteogenic benefits of different types of sports within their fields such as martial arts require further investigation, as a Malay study of adolescent male boxing, Muay Thai and Silat athletes indicated (Abidin et al, 2018;Norsuriani & Ooi, 2018). Another QUS study of the phalanges (hands) study of karate players found high QUS measurements (Norsuriani & Ooi, 2018).…”
Section: Sportsmentioning
confidence: 99%
“…The osteogenic benefits of different types of sports within their fields such as martial arts require further investigation, as a Malay study of adolescent male boxing, Muay Thai and Silat athletes indicated (Abidin et al, 2018;Norsuriani & Ooi, 2018). Another QUS study of the phalanges (hands) study of karate players found high QUS measurements (Norsuriani & Ooi, 2018).…”
Section: Sportsmentioning
confidence: 99%